Analisis QiyÄs Transaksi Tawarruq dengan Baiâ€™ al-â€™Äªnah - Komarudin, Parman; Hidayatullah, Muhammad Syarif (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2021)
This paper aimed to analyze the application of qiyas method in the prohibition of tawarruq transactions through qiyas tawarruq with bai' al-‘înah. This paper was qualitative research with a type of normative law research using conceptual approach. The results of paper showed that the application of the pillars of qiyas in qiyas tawarruq with bai' al-‘înah namely: bai' al-‘înah as ashl, tawarruq as far', the prohibition of bai' al-‘înah practice as hukm al-ashl and the main motive of the transaction in the form of obtaining cash (liquidity) instead of owning goods (commodities) with the mechanism of buying and selling and debt that represents hilah ribawiyah is as 'illat. Therefore, as is the prohibition against bai' al-‘înah, as it also applies to tawarruq. However, there is also a difference between bai' al-‘înah and tawarruq on the grounds of differences between the parties who make the second purchase, and some allow tawarruq on the condition that there is an urgent need or no agreement with a third party. Thus, it is very important in positioning ushul fiqh relevant to contemporary economy and finance, because the muamalah in Islam has flexibility, elasticity and openness to the development of the times.